Entrepreneurial Selves : Neoliberal Respectability and the Making of a Caribbean Middle Class - Freeman, Carla (Book collections on Project MUSE., 2014)
Steeped in more than a decade of ethnography on the emergent middle class of Barbados, this remarkable book turns a spotlight on the entrepreneur, a figure saluted across the globe as the very embodiment of neoliberalism.